Patterns of contemporary gene flow suggest low functional connectivity of grasslands in a fragmented agricultural landscape. Issue 2 (13th February 2013) - Aavik, Tsipe; Holderegger, Rolf; Edwards, Peter J.; Billeter, Regula
Summary: The success of ecological restoration is often judged by the number and abundance of species, especially rare ones that have established since restoration. However, the effects of habitat improvement upon connectivity are rarely assessed, although this can readily be performed using modern molecular genetic methods. We evaluated the functional connectivity of populations of a wet grassland plant Lychnis flos‐cuculi in an intensively managed agricultural landscape in Switzerland. One third of the study populations had been recently restored by sowing wildflower seed mixtures, while all other populations were of natural origin. We used assignment tests to identify first‐generation migrants and to estimate recent patterns of gene flow among the populations of L. flos‐cuculi . Assignment tests revealed higher levels of recent gene flow among natural populations of L. flos‐cuculi than between sown and natural populations. Most probably, this result simply reflected the formerly good connectivity of natural populations in the study landscape. We detected a few first‐generation migrants between sown and natural populations and among natural populations, suggesting that functional connectivity was now rather restricted. Migration among sown and natural populations was more likely to occur when natural and sown populations were nearby and when source populations were large. Synthesis and applications . We demonstrated that genetic methods offer a valuable tool for examining the effects of restoration measures on functional connectivity of plant populations. The connectivity of wet grasslands is likely to be best enhanced by establishing a relatively dense network of large habitat patches. Abstract : We demonstrated that genetic methods offer a valuable tool for examining the effects of restoration measures on functional connectivity of plant populations. The connectivity of wet grasslands is likely to be best enhanced by establishing a relatively dense network of large habitat patches.